المصارف الإسلاميّة ودورها في تمويل المشاريع التنمويّة الكبرى: دراسة حالة بيت التمويل الكويتي - محلق, عبد الغني; بن رجم, محمد خميسي; صيد, صابرة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى تسليط الضوء على مساهمة بيت التمويل الكويتي باعتباره أحد أكبر المصارف الإسلاميّة في العالم في تمويل المشاريع التنمويّة الكبرى، وقد توصّلت الدراسة إلى أنّ "بيتك" ساهم -على المستوى المحلي- في تمويل عدد كبير من المشاريع التنمويّة في مجالات عديدة من بينها: العقار والإنشاءات، البنيّة التحتيّة، قطاع البتروكيماويات، كما شارك أيضا -على الصعيد الإقليمي والدولي- في تمويل عدد من المشاريع الاستثماريّة والعقاريّة الكبرى وعدد من مشاريع البنيّة التحتيّة الضخمة The present study attempts to shed light on the contribution of Kuwait Finance House, being one of the largest Islamic banks in the world, in financing major development projects. The study concludes that “KFH” contributed - at the local level - in financing a large number of development projects in different fields, including: real estate and construction, infrastructure, petrochemicals sector. It also contributed, at the regional and international levels, in financing a fair number of major investment, real estate projects and a number of huge infrastructure projec
Islamic banks and their role in financing major development projects -Kuwait Finance House (KFH): case study
مقال
Keywords: المصارف الإسلاميّة، بيت التمويل الكويتي، تمويل المشاريع التنمويّة الكبرى.; Islamic banks, Kuwait Finance House, financing major development projects.